A new Masdevallia (Orchidaceae: Pleurothallidinae) from a deforested area in the Huanuco region of Peru - Dalström, Stig (2016)
A new and showy Masdevallia from the Huanuco region in Peru is described and illustrated with a line drawing and color photographs. It belongs to the subgenus Masdevallia, section Masdevallia. The new species is compared to several more or less morphologically similar species, such as M. burianii, M. cranion and M. popowiana that appear to be closely related. The new species differs from them by a combination of features, including the rather fleshy leaves and the bell-shaped flowers covered internally with magenta to white pubescence.